2023
DOI: 10.1108/jsm-05-2022-0179
|View full text |Cite
|
Sign up to set email alerts
|

Learning self-efficacies influence on e-servicescapes: rethinking post-pandemic pedagogy

Abstract: Purpose The post-pandemic recognises changes are required; universities need to rethink their e-servicescapes strategies by offering different approaches to enhance students’ learning. This study aims to draw on learning self-efficacy trajectories and propose a conceptual model for exploring the predictive validity of satisfaction. In addition, it explores the mediating role of e-servicescapes and the moderating relationship effect of mature and younger students. Design/methodology/approach Learning self-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…The mediation observed in this study was found to be significant only for competitive and independent learning styles. Interestingly, this mediation was only significant for competitive and independent learning styles, reflecting the findings of prior studies on the impact of individual learning styles on academic self-efficacy (e.g., D′Souza et al, 2023;Leow et al, 2021). However, the non-observed mediation effect across all learning styles suggests the complexity of these relationships and implies the existence of other potential influencing factors, such as past experiences with electronic assessments.…”
Section: Discussionsupporting
confidence: 56%
“…The mediation observed in this study was found to be significant only for competitive and independent learning styles. Interestingly, this mediation was only significant for competitive and independent learning styles, reflecting the findings of prior studies on the impact of individual learning styles on academic self-efficacy (e.g., D′Souza et al, 2023;Leow et al, 2021). However, the non-observed mediation effect across all learning styles suggests the complexity of these relationships and implies the existence of other potential influencing factors, such as past experiences with electronic assessments.…”
Section: Discussionsupporting
confidence: 56%
“…Learning self-efficacy refers to learners' self-determination and self-confidence that they will be able to achieve their academic goals in MOOCs context (D 'Souza et al, 2023). Past studies (Shiau et al, 2020;Susanto et al, 2016) have shown the influential roles of users' expectation confirmation and self-efficacy on continuous intention to use a product or service.…”
Section: Ijem 384mentioning
confidence: 99%
“…However, learning maladaptation is a widespread problem in blended learning environments with information technology applications [7][8]. Adaptation is not only a response to a new environment but also a long-term and continuous dynamic process of self-regulation to cope with changing environmental conditions [9][10], especially in blended learning environments; the challenge of adaptation is magnified, and its importance is amplified in the face of a large number of learners, different course contents and teaching resources, as well as changing environments [11][12][13]. Research has shown that learning adaptability is an important factor in determining the quality of student learning not only in blended learning environments but also in online environments [15].…”
Section: Introductionmentioning
confidence: 99%